Texture, Nutrition, and Flavor of Different Freshwater Fish Muscles: Comparative Study and Molecular Docking - Banghua Xia; Jiaming Zhang; Chenhui Li; Song Wu; Li Huang; Dongli Qin; Qirui Hao; Lei Gao (Foods, 2025)
Cyprinus carpio, Parabramis pekinensis, Aristichthys nobilis, and Lateolabrax maculatus were systematically evaluated as crucial components of Chinese aquaculture with substantial market demand. Texture profile analysis (TPA) showed C. carpio had maximal hardness, while L. maculatus displayed optimal elasticity. Nutrient composition analysis revealed that the highest crude protein content was identified in L. maculatus, while a higher crude lipid level was recorded in C. carpio. Fatty acid profiling established L. maculatus as a superior source of monounsaturated fatty acids (MUFAs), whereas P. pekinensis was distinguished by its polyunsaturated fatty acid (PUFA) content. Volatile compounds were comprehensively analyzed using an electronic nose (e-nose) coupled with HS-SPME-GC-MS, resulting in the identification of 59 flavor compounds. Molecular docking demonstrated that hydrogen bonding and π–π stacking were identified as critical mechanisms governing flavor perception. These findings offer valuable information that can support improvements in aquaculture management practices and help inform consumer choices regarding fish quality.